Analysis of Earthworm (Lumbricus rubellus) Growth Due to the Addition of Fruit Waste Pulp to Feed - Raksun, Ahmad; Merta, I Wayan; Mertha, I Gde (Jurnal Pijar Mipa, 2024)
Earthworms are a group of animals that live in soil and have a segmented body, bilaterally symmetrical, and covered by a transparent cuticle, which protects from physical and chemical disturbances. One of the factors that influences the growth of earthworms is the availability of food substances in the media where they live. Research on the analysis of the increase in the number and total weight of earthworms (Lumbricus rubellus) due to the provision of fruit waste in feed has been carried out in 2023. This research aims to analyse the increase in the number and total weight of earthworms due to the application of fruit waste to the media where earthworms live. Research data was analysed using variance analysis. In this study, the results were obtained: (1) fruit waste pulp (papaya and banana) added to feed had a significant effect on increasing the number of earthworms, (2) fruit waste pulp added to the feed can increase the total weight of earthworms, (3) Giving 2 liters of fruit waste to the feed results in a higher number and total weight of earthworms than other levels of fruit waste pulp.